The influence of personal value on the organizational change: a study at Majlis Amanah Rakyat / Syafiqah Athirah Ab Rahim - Ab Rahim, Syafiqah Athirah (2015)
The study is sought to evaluate the relationship between the dimension of personal values and the influence of the values on the organizational change. The participants were 200 individual working at Headquarter Majlis Amanah Rakyat, Kuala Lumpur. The literature review indications to the development of a conceptual framework that incorporate the influence of personal value (Openness to Change, Self-Enhancement, and Conservation) on the organizational change. Three hypotheses were proposed to be conducted in the study. Questionnaire will be distributed whereby the study uses quantitative data collection. A questionnaire was developed using literature review.